2010
DOI: 10.1111/j.1365-2265.2010.03821.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Association between 25‐hydroxyvitamin D, somatic muscle weakness and falls risk in end‐stage renal failure

Abstract: Suboptimal levels of 25OHD in CKD-5D are associated with reduced quadriceps muscle strength and increased falls risk. 25OHD may be more important than the active renal metabolite 1,25(OH)(2)D for muscle strength with implications for vitamin D choice and goals of supplementation. Further investigation is required to examine effectiveness of calciferol supplementation on the incidence of falls in CKD-5D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 52 publications
1
57
0
3
Order By: Relevance
“…However, contrasting results have been reported with high-dose therapy (37). In CKD-5D, lower 25(OH)D levels have been associated with quadriceps weakness and falls risk (18). In this study, baseline 25(OH)D levels correlated to the distance covered in a 6-minute walk test, but not to muscle strength, and no changes were detected over the study duration.…”
Section: Muscle Strength Functional Capacity and Hrqolmentioning
confidence: 52%
See 1 more Smart Citation
“…However, contrasting results have been reported with high-dose therapy (37). In CKD-5D, lower 25(OH)D levels have been associated with quadriceps weakness and falls risk (18). In this study, baseline 25(OH)D levels correlated to the distance covered in a 6-minute walk test, but not to muscle strength, and no changes were detected over the study duration.…”
Section: Muscle Strength Functional Capacity and Hrqolmentioning
confidence: 52%
“…Some of these actions may be mediated by local conversion of 25(OH)D to 1,25(OH) 2 D at target sites, including muscles, blood vessels and parathyroid glands (14,15). This could explain associations described in CKD-5D, between 25(OH)D levels and pulse wave velocity (PWV), a surrogate for vascular calcification (16), bone mineral density (17), early mortality on dialysis (6), muscle strength, falls risk, and quality of life (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged secretion of PTH results in the development of deep cavities between bone trabeculae 23 , causes loss of bone mass, and elevates fracture risks 24 , in addition to prompting an increase in the intracellular concentration of free calcium in muscle tissues 25,26 . Although a study by Boudville et al 20 , and this study did not find association between PTH levels and falling, some researchers observed that higher PTH levels are related to the latter 27,28 , considering that bone fragility, muscle weakness, and poor postural balance are independent risk factors for the occurrence of falls and fractures 29 . Therefore, high PTH levels associated with low vitamin D levels in individuals on hemodialysis cause a negative impact on muscle strength and functional mobility, because they cause the atrophy of muscle fibers of rapid concentration, thus predisposing the individuals to falling 11 .…”
Section: Risk Of Falling and The Parathyroid Hormonementioning
confidence: 61%
“…With regard to the association between the risk of falling and the PTH levels, only the use of the FES-I in the study conducted by Boudville et al 20 , was found. The researchers did not observe correlation between PTH serum levels and the FES-I, but they reported a higher tendency to fall among the patients who presented low calcitriol serum levels 20 .…”
Section: Risk Of Falling and The Parathyroid Hormonementioning
confidence: 99%
See 1 more Smart Citation